Effect of brief daily resistance training on rapid force development in painful neck and shoulder muscles: randomized controlled trial. (11th June 2013) - Jay, Kenneth; schraefel, mc; Andersen, Christoffer H.; Ebbesen, Frederik S.; Christiansen, David H.; Skotte, Jørgen; Zebis, Mette K.; Andersen, Lars L.
Summary Objective To determine the effect of small daily amounts of progressive resistance training on rapid force development of painful neck/shoulder muscles. Methods 198 generally healthy adults with frequent neck/shoulder muscle pain (mean: age 43·1 years, computer use 93% of work time, 88% women, duration of pain 186 day during the previous year) were randomly allocated to 2‐ or 12 min of daily progressive resistance training with elastic tubing or to a control group receiving weekly information on general health. A blinded assessor took measures at baseline and at 10‐week follow‐up; participants performed maximal voluntary contractions at a static 90‐degree shoulder joint angle. Rapid force development was determined as the rate of torque development and maximal muscle strength was determined as the peak torque. Results Compared with the control group, rate of torque development increased 31·0 Nm s−1 [95% confidence interval: (1·33–11·80)] in the 2‐min group and 33·2 Nm s−1 (1·66–12·33) in the 12‐min group from baseline to 10‐week follow‐up, corresponding to an increase of 16·0% and 18·2% for the two groups, respectively. The increase was significantly different compared to controls (P<0·05) for both training groups. Maximal muscle strength increased only ~5–6% [mean and 95% confidence interval for 2‐ and 12‐min groups to control, respectively: 2·5 Nm (0·05–0·73) and 2·2 Nm (0·01–0·70)]. No significant differences between the 2‐ and 12‐min groups were evident. A weak but significant relationship existed between changes in rapid force development and pain (r = 0·27, P<0·01), but not between changes in maximal muscle strength and pain. Conclusion Small daily amounts of progressive resistance training in adults with frequent neck/shoulder pain increases rapid force development and, to a less extent, maximal force capacity.